The Dynamics of Housing Allowance Claims in Sweden: A discrete-time hazard analysis - Jie Chen (Uppsala University, Department of Economics, 2006)
This paper analyses the dynamics of the duration of housing allowance claims in Sweden during the period 1991 to 2002. The central concern in this paper is whether the Swedish housing allowance system creates dependence on welfare. Using longitudinal data from Swedish micro database-LINDA, this paper found that there is no evidence of negative duration dependence arising from the duration of housing allowance claims. This finding is consistent across different model specifications and various controls of the heterogeneity issue. Hence we come to the conclusion that a recipients exit rate from the system does not decrease over the duration claim. This paper also shows that the demographic characteristics, educational background, labour market status and economic contextual conditions play important roles in determining recipients conditional probability of exiting from the housing allowance system. However, there are substantial variations in the factors impact across different household types.
urn:nbn:se:uu:diva-83064
Keywords: H24; I38; R21; 330; housing allowance; discrete-time hazard; duration dependence; Wohngeld; Öffentliche Sozialleistungen; Sozialpsychologie; Wirkungsanalyse; Öffentliche Sozialleistungen; Schweden